On the feasibility of utilizing active personal dosimeters worn on the chest to estimate occupational eye lens dose in x-ray angiography. (18th March 2015) - Omar, Artur; Marteinsdottir, Maria; Kadesjö, Nils; Fransson, Annette
Abstract: The International Commission on Radiological Protection (ICRP) has recommended that the occupational dose limit to the eye lens be substantially reduced. To ensure compliance with these recommendations, monitoring of the occupational eye lens dose is essential in certain hospital work environments. For assessment of the eye lens dose it is recommended to use a supplementary dosimeter placed at a position adjacent to the eye(s). Wearing a dosimeter at eye level can, however, be impractical and distributing and managing additional dosimeters over long periods of time is cumbersome and costly for large clinical sites. An attractive alternative is to utilize active personal dosimeters (APDs), which are routinely used by clinical staff for real-time monitoring of the personal dose equivalent rate ( H p (10)). In this work, a formalism for the determination of eye lens dose from the response of such APD's worn on the chest is proposed and evaluated. The evaluation is based on both phantom and clinical measurements performed in an x-ray angiography suite for interventional cardiology. The main results show that the eye lens dose to the primary operator and to the assisting clinical staff can be conservatively estimated from the APD response as and, respectively. However, care should be exercised for particularly short assisting staff and if radiation protection shields are misused. These concerns can be greatly mitigated if the clinical staff are provided with adequate radiation protection training.